Acidic conditions enhance the removal of sulfonamide antibiotics and antibiotic resistance determinants in swine manure. (August 2020) - Lin, Hui; Sun, Wanchun; Yu, Qiaogang; Ma, Junwei
Abstract: Manure pH may vary depending on its inherent composition or additive contents. However, the effect of pH on the fate of antibiotics and antibiotic resistance determinants in manure remains unclear. This work demonstrated that pH adjustment promoted the removal of different sulfonamide antibiotics (SAs) within swine manure under incubation conditions, which increased from 26–60.8% to 75.0–86.0% by adjusting the initial pH from neutral (7.4) to acidic (5.4–4.8). Acidification was also demonstrated to inhibit the accumulation of antibiotic resistance genes in manure during incubation. Acidified manure contained both lower absolute and relative abundances of sul1 and sul2 than those at a neutral pH like 7.4. Further investigation indicated that acidification promoted the reduction of sul genes in manure by restricting sulfonamide-resistant bacteria (SRB) proliferation and inhibiting IntI1 accumulation. Furthermore, pH adjustment significantly influenced the composition of the manure bacterial community after incubation, which increased Firmicutes and decreased Proteobacteria. Close relationships were observed between pH-induced enrichment of the Firmicutes bacterial phylum, enhanced SAs degradation, and the fates of antibiotic resistance determinants. Overall, lowering the pH of manure promotes the degradation of SAs, decreases sul genes and SRB, and inhibits horizontal sul gene transfer, which could be a simple yet highly-effective manure management option to reduce antibiotic resistance. Graphical abstract: Image 1 Highlights: Acidification induced an enrichment of Firmicutes in swine manure. It enhanced the removal of sulfonamide antibiotics. It inhibited the accumulation of sul genes, IntI1 and resistant bacteria. Abstract : Lowering the pH of manure promotes Firmicutes enrichment, sulfonamides degradation, and reductions in sul genes, IntI1 and sulfonamides-resistant bacteria.